Upaya Meningkatkan Hasil Belajar Fiqih Dengan Menggunakan Strategi Quick Short Di Kelas VII MTs. Swasta Darul Arafah Pangkalan Berandan - Nur Azizah, Usmaidar, Ahmad Zaki (Cybernetics: Journal Educational Research and Social Studies, 2023)
This study aims to determine the increase in student learning outcomes by learning the Quick Short Strategy at the Darul Arafah Private Madrasah Tsanawiyah Pangkalan Berandan. This type of research is classroom action research. The object of this research is to improve student learning outcomes through the Quick Short Strategy in class VII Madrasah Tsanawiyah Private Darul Arafah Pangkalan Berandan. The research subjects were students of class VII.1, totaling 39 people. Before the action is carried out, observations are made which include giving tests and interviews to class teachers to find out the activities and student learning outcomes. The data provided was obtained from sheets from observation sheets of activities, attitudes, and student learning outcomes in the form of questions and descriptions given. The test is given twice at the end of each cycle. After being given action through the Quick Short Strategy in class action research carried out in class VII Madrasah Tsanawiyah Private Darul Arafah Pangkalan Berandan from the results of observations of student learning activities in cycle II there was an increase compared to cycle I. In cycle I the first meeting student learning outcomes obtained an average value average 63, 58 and the second meeting of student learning outcomes obtained an average value of 67, 30. In the second cycle the average learning outcomes increased, the first meeting of student learning outcomes obtained an average of 70, 20 and the second meeting of student learning outcomes obtained an average - average 75.00. From the results of the pre-test before the action obtained an average value of 67.61 and the results of the post-test after the action obtained an average value of 78.23. If measured by N-gain the average student's ability is 0.32 in the medium category. This shows that the Quick Short Strategy according to Darul Arafah Pangkalan Berandan Private Madrasah Tsanawiyah students is considered good, namely between 56-75% classification. Thus the application of the Quick Short Strategy can improve student learning outcomes.